2019
DOI: 10.3389/fnmol.2019.00126
|View full text |Cite
|
Sign up to set email alerts
|

Tubgcp3 Is Required for Retinal Progenitor Cell Proliferation During Zebrafish Development

Abstract: The centrosomal protein γ-tubulin complex protein 3 (Tubgcp3/GCP3) is required for the assembly of γ-tubulin small complexes (γ-TuSCs) and γ-tubulin ring complexes (γ-TuRCs), which play critical roles in mitotic spindle formation during mitosis. However, its function in vertebrate embryonic development is unknown. Here, we generated the zebrafish tubgcp3 mutants using the CRISPR/Cas9 system and found that the tubgcp3 mutants exhibited the small eye phenotype. Tubgc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The TUBGCP3 (Tubulin Gamma Complex Associated Protein 3) is an important part of Gamma-tubulin complex, which is necessary for microtubule nucleation at the centrosome. 26 Previous studies have reported that TUBGCP3 plays a vital part in forming the structural constituent of cytoskeleton and microtubule nucleation by interphase microtubule organizing center. 27 It is well established that circRNAs originate from a series of exons.…”
Section: Discussionmentioning
confidence: 99%
“…The TUBGCP3 (Tubulin Gamma Complex Associated Protein 3) is an important part of Gamma-tubulin complex, which is necessary for microtubule nucleation at the centrosome. 26 Previous studies have reported that TUBGCP3 plays a vital part in forming the structural constituent of cytoskeleton and microtubule nucleation by interphase microtubule organizing center. 27 It is well established that circRNAs originate from a series of exons.…”
Section: Discussionmentioning
confidence: 99%
“…involved with eye morphological alterations(Du et al, 2015;Ergun et al, 2017;Li et al, 2019). Thus, this agnostic analysis of rare nonsense variants successfully identified candidate genes in A/M.…”
mentioning
confidence: 84%
“…and found evidence that each is involved in eye development(Bergman et al, 2012;Du et al, 2015;Ergun, Akay, Ergun, & Percin, 2017;Li, Jin, & Zhong, 2019;Meijer, 1993;Papakostas et al, 2018). For example, LRP5, NUMA1 and TUBGCP3 have been identified to be involved in retinal development and KRT31 to be…”
mentioning
confidence: 99%
“…Similar to lethality and abnormality effects study, all of the embryos were divided into four groups for this immunohistochemistry (IHC) analysis [ 59 ]. In this analysis, the protein expressions of DNA damages and apoptosis were investigated.…”
Section: Methodsmentioning
confidence: 99%